Práticas culinárias de terreiro: possibilidades para o turismo criativo gastronômico na Região Imperial Carbonífera do Rio Grande do Sul - Souza, Jean Júnior de (My University, 2025)
For this research, it is considered that: [a] gastronomy, including culinary practices, is part of the criteria proposed in the creative economy as an instrument for the economic development of cities and regions, in this case through Creative Tourism; [b] that seven of the eight municipalities that make up the Imperial Carboniferous Region of Rio Grande do Sul are among those with the lowest Human Development Index in the state, a situation in which Creative Gastronomic Tourism could activate local production chains; [c] that the Nations of African origin, known as Batuque in Rio Grande do Sul, in this case with emphasis on the Ijexá Nation, have a significant presence in the municipalities of the Imperial Carboniferous Region, in religiosity practiced in various terreiros, associating the religious with the processes of cultural expression, especially with regard to their ritualistic culinary practices. It therefore follows the Epistemology of the Macumbas as a transforming and empowering principle for research that has in its theoretical framework the ritualistic practices of religiosities of African origin, playing with the figure of the researcher-cambono, the one who observes, questions, presentifies the relationships within a terreiro. The aim is to analyze the culinary practices present in the Batuque of two cities in the Imperial Carboniferous Region, in their historical roots, their contemporary local adaptations and their possibilities for the Creative Gastronomic Tourism segment, incorporating the Creative Economy. It emerges that, despite belonging to the same nation, the interviewees practice different cuisines. For Tourism, this opens up opportunities for growth and potential in terms of souvenirs, terreiro culinary practices and the production of emblematic terreiro dishes. [resumo fornecido pelo autor]
Para esta pesquisa, considera-se que: [a] a gastronomia e nela incluso as práticas culinárias, integram os critérios propostos na economia criativa como instrumento de desenvolvimento econômico de cidades e regiões, no caso, através do Turismo Criativo; [b] que sete dos oito municípios que integram a Região Imperial Carbonífera do Rio Grande do Sul estão entre os de menor Índice de Desenvolvimento Humano do Estado, situação em que o Turismo Criativo Gastronômico poderá acionar cadeias produtivas locais; [c] que as Nações de matriz africana, denominadas de Batuque no Rio Grande do Sul, no presente caso com ênfase na Nação Ijexá, apresentam presença significativa nos municípios da Região Imperial Carbonífera, em religiosidade praticada em diversos terreiros, associando o religioso aos processos de expressão cultural, em especial no que se refere às suas práticas culinárias ritualísticas. Portanto, segue-se a Epistemologia das Macumbas como princípio transformador e potencializador de pesquisas que tenham em seu arcabouço teórico as práticas ritualísticas das religiosidades de matriz africana, brincando com a figura de pesquisador-cambono, aquele que observa, questiona, presentifica as relações dentro de um terreiro. Objetiva-se analisar as práticas culinárias presentes no Batuque de duas cidades, na Região Imperial Carbonífera, em suas raízes histórias, em suas adaptações locais contemporâneas e em suas possibilidades para o segmento de Turismo Criativo Gastronômico, incorporando a Economia Criativa. Encaminha-se que, apesar de pertencerem a mesma Nação, os entrevistados praticam culinárias de terreiro distintas. Para o Turismo, abre-se oportunidades de crescimento e potencialidades, quanto a questões relacionadas a souvenirs, práticas culinárias de terreiro e a produção de pratos emblemáticos dos terreiros. [resumo fornecido pelo autor]
Keywords: Turismo e gastronomia - Rio Grande do Sul; Economia; Batuque (Culto); Culinária africana; Turismo - Rio Grande do Sul; Tourism and gastronomy - Rio Grande do Sul (Brazil); Economics; Batuque (Cult); Cookery, African; Tourism - Rio Grande do Sul (Brazil)